The effect of internet user behavior on effective marketing via online group buying in Taiwan - Nara Pristiwa; Wan-Tran Huang; Desi Ayuningtyas (Proceedings of AICS - Social Sciences, 2017)
In recent years, online group buying is mushrooming in Taiwan. The effort among them, the way of their marketing to get consumers to join their group buying is to be an interesting discussion. This study explores internet user behavior as a factor in effective marketing in online group buying. There is some internet user behavior variables such as age, gender, the easiness of internet media, purposed security and information provision which should be considered by online purchase company. According to those previous studies, this research employs those internet user behavior factors. Also, a provision which should be considers the frequency of internet user on using internet media and purchase product mostly buy as others internet user behavior. Research data were collected by hand paper survey from March to May 2016. They are distributed to four areas: northern, eastern, central and southern of Taiwan and as many as 324 consumers had completed and returned questionnaires to be used. This research employs descriptive analysis and Pearson's product moment correlation to analyze the data. This study found there are correlations among online group buying companies should consider it to improve their profit sales.